Pengaruh Pencelupan Panas Terhadap Umur Patah dan Laju Korosi ASTM A36 Dalam Aluminium 7xxx - Nurhabibah Paramitha Eka Utami; Diah Kusuma Pratiwi (Jurnal Rekayasa Mesin, 2020)
The hot dipping method is one of the most commonly chosen measures to protect material from corrosion. The main objective of this study was to analyze the effect of hot dipping time variation in Aluminum 7xxx on corrosion resistance and fracture life of ASTM A36 by conducting corrosion testing, weight reduction measurements and fatigue test analysis. Corrosion test results show that the specimen with a hot dipping time of 2 minutes has a lower corrosion rate and less weight reduction. Observation of age fracture in 1º stress level using Torsee's Torsion Repeated and Bending Fatigue Machine shows that specimens with hot dipping time of 2 minutes in Aluminum 7xxx have a higher fatigue toughness value than specimens with hot dipping time of 1 minute in Aluminum 7xxx and non hot dipping specimens.